Quaternary of Scotland. - Wimbledon, W. A. (Springer Netherlands, 1993)
In describing the geomorphological heritage of Scotland, this volume offers a remarkable account of how the natural environment responded in terms of landforms, processes and plant communities, to severe climatic change as the Quaternary era progressed over the last two million years. This legacy, as preserved in the 138 nationally important GCR sites described, documents a remarkable diversity of landforms in a relatively small area. The rugged highland contrast with the rolling hills and flat plains found further south, while the western and northern islands, together with the highly-indented coastline add further to the scenic diversity. How this variety of landscapes came into being, the forces which shaped it, and the climatic extremes which drove it, are the themes explored in this volume.